2020
DOI: 10.21203/rs.3.rs-15418/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colonization of Arbuscular mycorrhizal fungi improve salinity tolerance of Eucalyptus (Eucalyptus camaldulensis Dehn.) seedlings

Abstract: Background: Soil salinity is an important problem for agriculture and effecting in the inability to use soil for cultivation. High salt levels reduce plant performance. Arbuscular mycorrhizal fungi (AMF) have been reported to enhance the tolerance of plants under salinity stress. For promote cultivation of economic plant in salt stress area that univariable to use to produce raw material for pulp industry. We determined the effects of AMF on the growth and nutrient status of eucalyptus (Eucalyptus camaldulensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Despite the greater AMF colonization, the lowest soil fungal community, evaluated by quantitative PCR, was observed for E. urophylla and there were negative correlations with the majority of other soil microbe indicators (discussed in the next section). In this survey, we found species-specific influences of Eucalyptus on mycorrhizal traits (spore number and root colonization), as observed by other authors ( Soumare et al., 2015 ; Klinsukon et al., 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Despite the greater AMF colonization, the lowest soil fungal community, evaluated by quantitative PCR, was observed for E. urophylla and there were negative correlations with the majority of other soil microbe indicators (discussed in the next section). In this survey, we found species-specific influences of Eucalyptus on mycorrhizal traits (spore number and root colonization), as observed by other authors ( Soumare et al., 2015 ; Klinsukon et al., 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…These AMF-treated plants under drought stress exhibited significantly higher root-hair density, length, and diameter in taproot and lateral roots. Klinsukon et al (2021) reported colonization by AMF (Glomus sp., Gigaspora albida, and Gigaspora decipiens) improved salinity tolerance of eucalyptus plants by increasing photosynthetic pigments and K/Na ratio, while reducing proline accumulation. Another study by Li et al (2020) reported alleviation of moderate salinity stress (100 and 150 mM) in Euonymus maackii (an important ecological restoration tree) by AMF (Rhizophagus intraradices) as improved photosynthesis, plant nutrient absorption, and antioxidant enzyme activities were observed.…”
Section: Drought and Salinitymentioning
confidence: 99%